UPAYA BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) DI PADANG DALAM MENGAWASI PEREDARAN MAKANAN KEMASAN - Desi Arisanti; Dasman Lanin; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
This study discusses how the efforts of the Food and Drug Supervisory Agency (BBPOM) in Padang to oversee the circulation of packaged food, as well as see how the supervision and obstacles faced by BBPOM to overcome this circulation.In reality, there were still various packaging foods that were dangerous to consumefound in the Padang City, such as expiration, the useof hazardous materials, illegal marketing authorization, etc. This study used descriptive qualitative method. Data in this study were collected through observation, interview, and documentation study. Informants in this study were determined through purposive sampling technique. Then the data were analyzed with interactive analysis model consisted of data collection, data reduction, data classification, data presentation and conclusion/verification. The results of this research showed that various efforts had been carried out by BBPOM in Padang to supervise the outstanding packaged foods, but this monitoring effort had not run optimally. This could be seen from the fact that the BBPOM still found some shops (stores) in the PadangCity, which was selling expired or illegal goodsand without legal distribution licenses.